3D Nanostar Dimers with a Sub‐10‐nm Gap for Single‐/Few‐Molecule Surface‐Enhanced Raman Scattering. (22nd January 2014) - Chirumamilla, Manohar; Toma, Andrea; Gopalakrishnan, Anisha; Das, Gobind; Zaccaria, Remo Proietti; Krahne, Roman; Rondanina, Eliana; Leoncini, Marco; Liberale, Carlo; De Angelis, Francesco; Di Fabrizio, Enzo
<x xml:space="preserve">Abstract</x> Plasmonic nanostar‐dimers, decoupled from the substrate, have been fabricated by combining electron‐beam lithography and reactive‐ion etching techniques. The 3D architecture, the sharp tips of the nanostars and the sub‐10 nm gap size promote the formation of giant electric‐field in highly localized hot‐spots. The single/few molecule detection capability of the 3D nanostar‐dimers has been demonstrated by Surface‐Enhanced Raman Scattering. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>